THE CHANGE INDICES OF SOLAR AND GEOMAGNETIC ACTIVITY AND THEIR INFLUENCE ON THE DINAMICS OF DRAG OF ARTIFICIAL SATELLITE - Komendant, V. H.; Koshkin, N. I.; Ryabov, M. I.; Sukharev, A. L. (Одеські астрономічні публікації, 2016)
The time-frequency and multiple regression analysis of the orbital parameter characterizing the drag of satellites on circular and elliptical orbits with different perigees and orbital inclinations in the atmosphere of the Earth was being conducted in 23-24 cycles of solar activity. Among the factors influencing braking dynamics of satellites were taken: W – Wolf numbers; Sp – the total area of sunspot groups of the northern and southern hemispheres of the Sun, F10.7 – the solar radio flux at 10,7 cm; E – electron flux with energies more than 0,6 MeV и 2 MeV; planetary, high latitude and middle latitude geomagnetic index Ap. In the atmospheric drag dynamics of satellites, the following periods were detected: 6–year, 2.1–year, annual, semi-annual, 27–days, 13– and 11–days. Similar periods are identified in indexes of solar and geomagnetic activity. Dependence of the periods of satellites motion on extremes of solar activities and space weather conditions was conducted.